Neuroprotective effect of Bouvardia ternifolia (Cav.) Schltdl via inhibition of TLR4/NF-κB, caspase-3/Bax/Bcl-2 pathways in ischemia/reperfusion injury in rats - Yury Maritza Zapata-Lopera; Yury Maritza Zapata-Lopera; Gabriela Trejo-Tapia; Edgar Cano-Europa; Aida Araceli Rodríguez-Hernández; Placido Rojas-Franco; Maribel Herrera-Ruiz; Enrique Jiménez-Ferrer (Frontiers Media S.A., 2024)
IntroductionBouvardia ternifolia is a plant known for its traditional medicinal uses, particularly in treating inflammation and oxidative stress. Recent studies have explored its potential in neuroprotection, especially in the context of cerebral ischemia/reperfusion injury, a condition where blood supply returns to the brain after a period of ischemia, leading to oxidative stress and inflammation. This damage is a major contributor to neuronal death and neurodegenerative diseases.MethodsA BCCAO/reperfusion model was induced, followed by treatment with B. ternifolia extract. Various molecular biology methods were employed, including Western blot analysis, gene expression assessment via RT-qPCR, and the measurement of oxidative stress mediators.ResultsIn the BCCAO/reperfusion model, the compounds in the dichloromethane extract work by targeting various signaling pathways. They prevent the activation of iNOS and nNOS, reducing harmful reactive oxygen and nitrogen species, and boosting antioxidant enzymes like catalase and superoxide dismutase. This lowers oxidative stress and decreases the expression of proteins and genes linked to cell death, such as Bax, Bcl-2, and caspase-3. The extract also blocks the TLR4 receptor, preventing NF-κB from triggering inflammation. Additionally, it reduces the activation of microglia and astrocytes, as shown by lower levels of glial activation genes like GFAP and AiF1.ConclusionThe dichloromethane extract of B. ternifolia demonstrated significant neuroprotective effects in the BCCAO/reperfusion model by modulating multiple signaling pathways. It effectively reduced oxidative stress, inhibited inflammation, and attenuated apoptosis, primarily through the downregulation of key proteins and genes associated with these processes. These findings suggest that the extract holds therapeutic potential for mitigating ischemia/reperfusion-induced neuronal damage.